Sex, drugs, and Salmonella: rendezvous in the colon - Schwerdtfeger, Luke, author; Ryan, Elizabeth, author; Tobet, Stuart, author (Colorado State University. Libraries, 2017)
Intestinal infections impact millions of people each year, often with ineffective treatments available. There is a lack of models capable of studying these infections that recapitulate the guts cellular environment. Addressing this, we placed biopsies from human colon into culture, and maintained the cellular environment observed in vivo, in a dish. Using this model, sex differences in colonic T-cell responses to Salmonella were observed. When culturing biopsy tissue at ~1% oxygen there was an increase in epithelial cell birth compared to atmospheric oxygen. These results signal the need for controlling oxygen and tracking sex when studying colon-microbiome interactions. Purpose: Mammalian intestines maintain a highly complex physiology that survives an extreme oxygen gradient, a mixed population of commensal and pathogenic bacteria, and a heterogeneous cell composition that includes immune, neural, and epithelial elements. Understanding disorders and developing treatment modalities for intestinal disease and infection states requires balancing multiple factors, including sex-dependence. This study begins to account for the impacts of oxygen concentrations in the context of sex, pathogen, and antibiotic exposure. Procedure: Organotypic slices from human colon biopsies provided three-dimensional environments that maintained cellular morphology and relationships, ex vivo. Biopsy slices were used to study impacts of pathogen exposure on lymphocyte counts, and oxygen and antibiotic treatments on epithelial proliferation rates. Results: Sex differences were observed in basal CD3+ T lymphocyte count in human colon, with male patients having over 2-fold more CD3+ T cells than females. When exposed to a strain of Salmonella enterica, male cell counts did not change, while there was a significant increase in CD3+ T cells in biopsy slices taken from females (P < 0.05). For intestinal mucosa, there were greater rates of epithelial cell proliferation in lowered oxygen conditions (1%) than under more standard atmospheric conditions (20%)(P < 0.05). Antibiotic treatment decreased epithelial proliferation in slices maintained in 1% oxygen, but not 20% (P < 0.05). Implications: These results show a baseline T cell sex difference in the human colon that showed a sex-dependent response to pathogen ex vivo. In addition, oxygen concentration impacted colonic epithelial cell proliferation. Together, these results point towards the need to account for oxygen concentration and sex when studying gut-microbe interactions.
253 - Luke Allen Schwerdtfeger